Plasma Cytokines and Birth Weight as Biomarkers of Vaccine-Induced Humoral Responses in Piglets - Lipsit, Sean; Facciuolo, Antonio; Scruten, Erin; Griebel, Philip; Napper, Scott (Frontiers in Veterinary Science, 2022)
Failure to mount an effective immune response to vaccination leaves individuals at risk for infection and can compromise herd immunity. Vaccine unresponsiveness can range from poor responses “low responders” to a failure to seroconvert “non-responders”. Biomarkers of vaccine unresponsiveness, particularly those measured at the time of vaccination, could facilitate more strategic vaccination programs. We previously reported that pro-inflammatory cytokine signaling within peripheral blood mononuclear cells, elevated plasma interferon-gamma (IFNγ), and low birth weight correlated with vaccine-induced serum IgG titers in piglets that were below the threshold of detectable seroconversion (vaccine non-responders). These observations suggested that plasma IFNγ concentration and birth weight might serve as pre-vaccination biomarkers of vaccine unresponsiveness. To test this hypothesis, piglets (n=67) from a different production facility were vaccinated with the same commercial Mycoplasma hyopneumoniae bacterin (RespiSure-One) to determine if there was a consistent and significant association between vaccine-induced serum IgG titers and either plasma cytokine concentrations or birth weight. All piglets seroconverted following vaccination with significantly less variability in vaccine-induced serum IgG titers than observed in the previous vaccine trial. Piglets exhibited highly variable birth weights and plasma cytokine concentrations prior to vaccination, but there were no significant associations (p>0.05) between these variables and vaccine-induced serum IgG titers. There were significant (p<0.001) differences in plasma IFNγ concentrations among individual litters (n=6), and plasma IFNγ concentrations decreased in all pigs from birth to 63-days of age. One of the six litters (n=11 piglets) exhibited significantly elevated plasma IFNγ concentrations during the first three weeks of life (p<0.001) and at the time of vaccination (p<0.01). This litter, however, had similar vaccine-induced serum IgG titers when compared to the other piglets in this study. Collectively the two studies indicate that while plasma cytokines and birth weight can be associated with vaccine non-responsiveness, their temporal and individual variation, as well as the complexity of the vaccine responsiveness phenotype, make them inconsistent biomarkers for predicting the less extreme phenotype of vaccine low responders.